Quantitative assessment of retinal microvascular remodeling in eyes that underwent idiopathic epiretinal membrane surgery - Shen, Yingjiao; Ye, Xin; Tao, Jiwei; Zhao, Chenhao; Xu, Zhaokai; Mao, Jianbo; Chen, Yiqi; Shen, Lijun (Frontiers in Cell and Developmental Biology, 2023)
Abstract Purpose: To explore the surgical outcomes of the macular microvasculature and visual function in eyes with idiopathic epiretinal membrane (iERM) using spectral-domain optical coherence tomography angiography (SD-OCTA). Methods: This observational, cross-sectional study included 41 participants who underwent iERM surgery with a 3-month (3M) follow-up. Forty-one healthy eyes formed the control group. The assessments included best-corrected visual acuity (BCVA) and mean sensitivity (MS) by microperimetry and SD-OCTA assessment of vessel tortuosity (VT), vessel density (VD), foveal avascular zone, and retinal thickness (RT). Results: The findings showed statistically significant differences in VT, foveal avascular zone parameters, RT, BCVA, and MS between the iERM and control groups (P < 0.05). After iERM surgery, the macular VT, SCP VD, and RT decreased significantly (P < 0.01) while the DCP VD increased (P = 0.029). The BCVA improved significantly (P < 0.001) and was associated with the MS (rs = -0.377, P = 0.015). MS was associated with the SCP VD and RT at 3M (SCP VD rs = 0.511, P = 0.001; RT rs = 0.456, P = 0.003). In the superior quadrant, the MS improved significantly (P < 0.001) and the improvement of MS was associated with the reduction of VT (β = -0.330, P = 0.034). Conclusion: Microcirculatory remodeling and perfusion recovery were observed within 3 months after iERM surgery. VT was a novel index for evaluating the morphology of the retinal microvasculature in eyes with iERM and was associated with MS in the superior quadrant.